Hepatitis C: Is a vaccine the solution? - Mehta, Bharti (Landes Bioscience, 2014)
Hepatitis C Virus (HCV) infection is a major cause of chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Following acute infection, 20% of people eliminate the virus over weeks or months and are often asymptomatic. The remaining 80% of people will develop chronic disease, of which approximately 20% will eventually develop liver cirrhosis and 1–5% will develop liver cancer. About 150 million people are chronically infected with HCV, and more than 350 000 people die every year from hepatitis C related liver diseases. The economic cost of hepatitis C is significant both to the individual and to the society. In the United States the average lifetime cost of the disease was estimated at $33 407 USD with the cost of a liver transplant approximately $200 000 USD. PEG-IFN and ribavirin treatment is also expensive and, at an average cost of approximately GB £7000 in the UK for a treatment course, is unaffordable in developing countries. Hepatitis C, not only brings down the quality of the life of individuals but also affect progress of the nation by adding financial burden. If we prevent the disease from occurring or find a perfect cure of the disease, in form of a prophylactic or therapeutic vaccine, it will be a boon to not only to the individual but to the nation as a whole.